The effect of educational intervention based on the mobile application on women’s knowledge, attitude, and practice on microplastics and health: study protocol for a randomized controlled trial - Zahra Seifi; Fatemeh Zarei; Fazlollah Ahmadi (Trials)
Abstract Background The pervasive issue of microplastic (MP) contamination is undeniable. The primary solution to this global problem lies in significantly reducing the amount of plastic entering the environment. Addressing such a large-scale issue is no easy feat. However, a necessary strategy involves public education. In parallel, a randomized controlled trial (RCT) aims to evaluate the effect of interventional education via a mobile phone application on improving women’s knowledge, attitude, and practice regarding the health effects of MPs. Methods This randomized controlled trial includes three phases. In the first phase, a questionnaire assessing women’s knowledge, attitudes, and practices (KAP) regarding microplastics will be developed and validated. In phase two, educational content for the mobile application “PlastiWise” will be created based on behavior change constructs. In phase three, a two-arm, parallel-design RCT will be conducted with 136 women aged 18 years and older who own smartphones, have basic literacy skills, and provide informed consent. Participants will be recruited through an online call disseminated via social media platforms and health system networks in Iran. They will be randomly assigned to an intervention group (n = 68) receiving the educational program through the app or a control group (n = 68). The sample size was calculated using G*Power software to ensure sufficient power (80%) with an alpha level of 0.05, factoring in a 15% dropout rate. Primary outcome data (KAP scores) will be collected at baseline, immediately post-intervention, and 8 weeks post-intervention using self-reported questionnaires. Data analysis will include descriptive statistics and inferential tests, such as independent t-tests and paired t-tests, to assess group differences and within-group changes over time. Discussion Implementing an educational intervention on knowledge, attitude, and practice (KAP) about MPs using a mobile application will be a first in Iran. This research is expected to benefit Iranian women by contributing evidence on factors that might influence the effectiveness of educational training related to MP consumption. Trial status  Protocol version 1, 2024–07-12. The enrolment of participants began on 2024–09-22. The recruitment is estimated to be completed by 2024–11-21. Trial registration  Iranian Clinical Trial Register IRCT20240529061941N1. https://irct.behdasht.gov.ir/user/trial/77069/view . Date is July 12, 2024.